Affiliate to Armed Forces Hospital in Jazan, Ministry of Defense Health Services Jazan, Saudi Arabia The Association between Healthcare Workers' Burnout Levels and Patient Satisfaction Scores - Shahad Mater Gofashy,Abeer Yahya Thamiri,Awad Ali Al Qahtani,Rabyeh Yahya Jaghdami,Ghalia Mohammed Aljathmi,Mada Yahya Abdu Qahl,Mudawi Ali Huraysi,Othman Ahmed Hakami,Ahmad Khaled Faqihi; Ali Mohammed Oberi,Mohammed Abdullah Moshe,Hassan Ahmed Alamri,Mohammed Omar Makin,Shaiban Mohammed Shajiri,Mohammed Jaber Alazzi (Journal of International Crisis and Risk Communication Research, 2024)
The relationship between healthcare workers' burnout levels and patient satisfaction scores represents a critical intersection in modern healthcare delivery that demands thorough examination. This intricate interplay has implications for the safety, satisfaction, and productivity of workers, the delivery of care, and, by extension, the health of consumers. As healthcare systems worldwide face increasing pressures from various sources including the aftermath of global health crises, staffing shortages, and rising administrative demands among others, it becomes incumbent for healthcare managers, policymakers, and practitioners to gain insights into the relationship between worker burnout and patient satisfaction. The healthcare industry paints a scary picture of how burnout, characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment can negatively affect the healthcare system and patients. The goal of this paper is to provide an overview of the bidirectional and dynamic link between healthcare worker burnout and patient satisfaction: the potential process through which, a promotion strategies.